Tour Operator Marketing Planning and Tourism Competitiveness in KwaZulu-Natal - Seymour, James CT (2009)
Competitive tourism destinations are those which constantly identify the core challenges affecting their performance and put measures into place to deal with these issues. In addition, they also identify opportunities innovatively to secure a distinctive or favourable position in the tourism marketplace. This dissertation identified the nature and extent of a destination’s inbound tour operator base, the level of strategic marketing planning of these operators, as well as the strength of the relationship of such entities with their destination management organisation as being an important factor which influences the level of competitiveness of a tourism area. The South African province of KwaZulu-Natal was identified as being a useful case study to test this assertion. KwaZulu-Natal has recently experienced a steady decline in its level of foreign tourism as opposed to its most important provincial competitors, the Western Cape and Gauteng. This is a province which has the dominant share of the South African domestic market and has a diverse of range of unique natural and cultural experiences. The broad aim of this study was thus to investigate KwaZulu-Natal’s inbound tour operators’ levels of marketing planning (strategic and action or annual), as well as to determine if there was a significant difference in the nature and level of planning of KwaZulu-Natal’s tour operators as opposed to that of their competitors in the Western Cape and Gauteng. This study demonstrated that this was the case, and that it may be one of the reasons why KwaZulu-Natal does not perform as well as Gauteng or the Western Cape from a foreign tourism perspective. Recommendations are also provided as to how the destination management organisation of this province could deal with this challenge. An example is the recommendation that Tourism KwaZulu-Natal should mobilise training programmes to introduce its inbound tour operators to the significance of strategic and annual marketing planning. It is suggested that such training have a practical format, with actual examples of successful tour operator business plans used and ideally assist SMEs with the formulation of their short and long term marketing plans.